Optimisation of the routing protocol for quantum wireless Ad Hoc network. Issue 1 (22nd November 2021) - Zhang, Ling; Liu, Qin
Abstract: This study addresses the optimisation of on‐demand routing protocols for quantum wireless Ad Hoc network. The study improves the route discovery protocol by proposing a 'reverse synchronisation method', which means after the route request is completed, the quantum channel establishment process can be carried out simultaneously with the route reply process. This method is better than the general method which builds quantum channels after the forward path establishment, reduces the time and the number of messages for quantum channel establishment, thus improving the efficiency. Accordingly, this study elaborates the specific methods, procedures and related upgrading message formats involved in quantum route discovery, quantum channel establishment and qubit information transmission of on‐demand routing protocol for quantum wireless Ad Hoc network.